Lagrangian water mass tracing from pseudo-Argo, model-derived salinity, tracer and velocity data: An application to Antarctic Intermediate Water in the South Atlantic Ocean. (January 2015) - Blanke, Bruno; Speich, Sabrina; Rusciano, Emanuela
Highlights: The focus of the study is on the AAIW circulation in the South Atlantic Ocean. We reconstruct a non-divergent 3D velocity field from pseudo-Argo, model-derived data. The algorithm uses only gridded velocity at 1000 m, vertical density profiles and wind stress. We reproduce the reference AAIW pathways calculated from the full model information. Lagrangian analyses using genuine, gridded Argo data are envisaged confidently. Abstract: We use the tracer and velocity fields of a climatological ocean model to investigate the ability of Argo-like data to estimate accurately water mass movements and transformations, in the style of analyses commonly applied to the output of ocean general circulation model. To this end, we introduce an algorithm for the reconstruction of a fully non-divergent three-dimensional velocity field from the simple knowledge of the model vertical density profiles and 1000-m horizontal velocity components. The validation of the technique consists in comparing the resulting pathways for Antarctic Intermediate Water in the South Atlantic Ocean to equivalent reference results based on the full model information available for velocity and tracers. We show that the inclusion of a wind-induced Ekman pumping and of a well-thought-out expression for vertical velocity at the level of the intermediate waters is essential for the reliable reproduction of quantitative Lagrangian analyses. Neglecting the seasonal variability of the velocity and tracer fields is not a significant source of errors, at least well below the permanent thermocline. These results give us confidence in the success of the adaptation of the algorithm to true gridded Argo data for investigating the dynamics of flows in the ocean interior.